The Influence of Institutional Ownership and Profitability to The Value of Property Company and Real Estate in Indonesia Stock Exchange - Rachmawati, Eka Nuraini; Saputra, Randi (Jurnal Ilmu Manajemen, 2016)
This research aims to analyze the influence of institutional ownership and profitability to the value of company. The financial work is measured by Return On Asset (ROA), the institutional ownership is measured by ratio of institutional ownership, and the value of company is measured by Tobins’Q. The object of this research is property company and real estate which are registered in Indonesia Stock Exchange from 2009 to 2012. Following this, this research uses multiple linear regression. Then the result shows that there is a positive influence of profitability to the value of company. It means that the higher number of Return On Asset (ROA) will increase the value of company. Meanwhile, the institutional ownership has a negative influence to the value of company. It means that the lower value of institutional ownership will increase the value of company.